Advanced virtual inertia control against wind power intermittency - Muhammad Abdillah; Syailendra Andi; Teguh Aryo Nugroho; Herlambang Setiadi (Institute of Advanced Engineering and Science, 2022)
Rapid industrial development requires more energy to support their manufacturing processes. Unfortunately, conventional energy was mostly utilized as a primary energy source which is unfriendly to nature and can damage the environment. Nowadays, the transformation from the use of conventional energy to renewable energy sources is increasingly being socialized throughout the world. However, the existence of renewable energy poses new challenges in the world of electricity systems where their effect is reducing the inertia (inertialess) value of conventional energy such as thermal generators. This condition causes frequency oscillations and leads to blackout the electricity system. To overcome this problem, this paper proposed advanced virtual inertia control (VIC) based on an superconducting magnetic energy storage (SMES) employed to accommodate the effects of the integration of renewable energy into the electric power system. SMES was choosen because it has a fast response and an efficiency rate of up to 90%. A two-area power system model was utilized to examine the proposed VIC model based on SMES. From the simulation results, VIC based on has succeeded in reducing frequency oscillations by compressing the system overshoot and reducing the settling time to steady-state.